(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The influence of the Muslim dispora in Europe continues to grow in parallel with the growth of its population. As a result of efforts in recent migration, Islam is becoming more common. In some European countries there are Islamic political parties, and many cities-Muslim regions and communities. The author tried to analyze the state of Islam in Europe at the moment, its controversial nature, bring information about the number of Muslims in the major countries. This article discusses the processes of adaptation of Muslims to European values, the preservation of their ethnic and religious identity. The author emphasizes that special concern is the fact that native Europeans (in particular youth) not only accept Islam as a faith, but also begin to replenish extremist organizations. This article also explores the prospects of EuroIslam or European Islam as a religious-ideological system. Key words: islam, Europe, muslims, Islamic factor, migration, identity, euroislam.